The Treatment of Renal Diseases (Res Medica, 2013)
All the well-known processes of pathology—acute and chronic inflammation, immune reactions, degenerative changes, etc.—may be found in the kidney, and the forms of therapy required to reverse them are equally diverse. All these processes, however, lead to one thing, destruction of renal tissue. This destruction may be rapid and severe, followed by regeneration in many cases, or a slow but progressive destruction with fibrous overgrowth.Broadly speaking, the kidneys are responsible for maintaining the stability of the body fluids. If acute destruction of renal tissue occurs the body fluids are acutely altered, whereas in chronic renal destruction the disturbance is slowly progressive. The acute upset of normal physiology accompanying rapid destruction is the syndrome known as acute renal failure, and the progressive physiological imbalance known as chronic renal failure is the result of chronic tissue destruction.This leads me to the first and most important point I wish to make. Therapy in renal disease must be two-fold. Firstly, it must deal with the pathological process causing renal destruction. Secondly, it must correct the disordered physiology which the renal disease has created. Whereas the pathological processes are legion, they lead to only two types of physiological upsets—acute or chronic renal failure.